The prevalence of sexual dysfunction among postpartum women on the East Coast of Malaysia - Khalid, Nur Nadrah; Jamani, Nurjasmine Aida; Abd. Aziz, Karimah Hanim; Draman, Nani (Elsevier Ltd on behalf of Taibah University, 2020)
Abstract Objective: Sexual health is a key component of the overall health and quality of life of both men and women. Sexual dysfunction is a common condition, but it lacks professional recognition. This study aims to determine the prevalence and types of sexual dysfunctions among postpartum women in primary care clinics and their associated factors in a Malaysian cohort. Method: In this cross-sectional study, we recruited 420 women from nine primary care clinics in Kuantan, Pahang, Malaysia. All participants had given livebirths within six weeks to six months and had attended either a postnatal or a well-child clinic at a government primary care clinic. The assessment of female sexual dysfunction (FSD) was done using a validated Malay version of the female sexual function index (MVFSFI). Data were statistically analysed using appropriate methods.